Den geografiska, funktionella och processorienterade organisationen : en fallstudie av Holmen Skog, SCA Skog och Sydkraft Vattenkraft - Bauer, Magnus (SLU/Dept. of Forest Products, 2003)
This thesis reports on a case study of two different organisational forms in the Swedish forest industry; the geographic and the functional organisation. The work in the geographic organisation is carried out within districts under the supervision of an overall responible district manager, where as in the functional organisation the work has been divided into functions headed by function managers. Forest magement, logging and wood purchases are examples of such functions. The general idea of the functional organisation is having the functions working over a larger geographic unit, without subdividing district boundaries of the region. Also a third organisational form of current interest for the forest industry; the process orientated organisation, is analyzed in the case study.